2022
DOI: 10.3390/life12122056
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Volatile Extracts from Black Raspberries, Blueberries, and Blackberries and Their Antiproliferative Effect on A549 Non-Small-Cell Lung Cancer Cells

Abstract: Berry volatiles are responsible for the berry aroma but there is limited information available on the health-promoting activities of berry volatiles. The objectives of this study were to evaluate the chemical composition of volatile extracts from black raspberries, blueberries, and blackberries and investigate their antiproliferative effect and apoptotic mechanisms on A549 lung cancer cells. The chemical composition of three berry volatile extracts (BVEs) was identified by using gas chromatography-mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A strong cytotoxic and cytostatic effect on tumor cells has been noted in both lines [33]. Volatile substances present in berry fruit extracts inhibit the proliferation of non-small-cell lung cancer A549 cells via the induction of apoptosis [10]. Raspberry fruits used in the diet exert a chemopreventive effect on colorectal cancer in patients with nonspecific inflammatory bowel disease.…”
Section: Anticancer Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong cytotoxic and cytostatic effect on tumor cells has been noted in both lines [33]. Volatile substances present in berry fruit extracts inhibit the proliferation of non-small-cell lung cancer A549 cells via the induction of apoptosis [10]. Raspberry fruits used in the diet exert a chemopreventive effect on colorectal cancer in patients with nonspecific inflammatory bowel disease.…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…The fruits of various Rubus species and other berries consumed as part of the diet can be used for the prophylaxis and adjuvant therapy of many diseases, mainly oxidative stress-induced conditions [6,7]. Rubus fruit phytochemicals exhibit a wide range of pharmacological activities, e.g., anti-obesity [8], anti-Alzheimer [9], antibacterial [6], anticancer [10], hepatoprotective [11], hypoglycemic [12], hypolipidemic [13], neuroprotective [14], against obesity [15], and skincare [16] effects.…”
Section: Introduction 1pro-health Antioxidant Activity Of Rubus Fruitsmentioning
confidence: 99%
“…Moreover, studies have also revealed that using raspberry extract stimulates the apoptosis of cervical cancer cells [ 67 ]. Furthermore, flavonoids (contained in blueberries) also show proapoptotic properties in breast and lung cancer cells [ 68 , 69 ].…”
Section: Raspberries Vs Apoptosis and Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…Anthocyanins have garnered significant scientific interest due to their potential health benefits. Epidemiological investigations have linked regular consumption of anthocyanin-rich foods (e.g., red cabbage [13], blueberry [14], and blackberry [15]) to a lower risk of some forms of cancer, including TNBC [16][17][18]. Out of the 700 different anthocyanin derivatives found in nature, only six are dominant, making up 90% of all known anthocyanins (cyanidin, delphinidin, malvidin, pelargonidin, peonidin, and petunidin) [11,13].…”
Section: Introductionmentioning
confidence: 99%